PENGARUH CITRA KOPERASI TERHADAP LOYALITAS ANGGOTA KOPERASI PADA KOPERASI SIMPAN PINJAM (KSP) JASA DI KABUPATEN KENDAL - TH Susetyarsi (JURNAL STIE SEMARANG, 2018)
The purpose of this research is to analyze the effect of cooperative image consisting of values ​​and principles and member transactions on the loyalty of cooperative members at KSP Services in Kendal Regency. In this study the population of 3,234 people, the sample used as many as 100 people. The method of analysis using multiple regression, coefficient of determination and t test and F test with the help of SPSS in the calculation. The results of this study indicate that the image of cooperatives consisting of values ​​and principles and member transactions on the loyalty of members of the cooperative in KSP Services in Kendal Regency have a positive influence.